KEMAMPUAN MENULIS CERITA PENDEK PADA SISWA KELAS X SMA NEGERI 1 GADINGREJO - Erwin Saputra; Nurlaksana Eko Rusminto; Muhammad Fuad (FKIP Universitas Lampung, 2013)
Issues discussed in this study was how the level of ability to write short stories in class X SMA Negeri 1 Gadingrejo second semester of academic year 2012/2013. Sample 10% of the total population as much as 253 students which are 24 students. The short story writing skills of students' a class X SMA Negeri 1 Gadingrejo school year 2012/2013, belong to the category of fairly with an average score of 70,67. Score per indicator 1) the theme score of 69,45 category enough; 2 a) the figures that were presented score of 85,58 excellent category, b) the presentation of the character figures score of 64,04 fair category; 3) background score of 65,5 category of pretty; 4 a) a series of events 71,66 category enough, b) the flow of the game score of 66.88, enough categories; and 5) style language score of 71,63 category enough.Masalah yang dibahas dalam penelitian ini adalah bagaimana tingkat kemampuan menulis cerita pendek pada siswa kelas X SMA Negeri 1 Gadingrejo semester genap tahun pelajaran 2012/ 2013. Sample diambil 10% dari populasi yang berjumlah 253 siswa yakni 24 siswa. Hasil kemampuan menulis cerita pendek siswa kelas X SMA Negeri 1 Gadingrejo tahun pelajaran 2012/2013, tergolong dalam kategori cukup dengan skor rata-rata 70,67. Skor rata-rata kemampuan siswa perindikator adalah: 1) tema skor rata-rata 69,45 kategori cukup; 2 a) tokoh yang dihadirkan skor rata-rata yaitu 85,58 kategori sangatbaik, b) penyajian watak tokoh skor rata-rata 64,04 kategori cukup; 3) latar dengan rata-rata 65,5 kategori cukup; 4 a) rangkaian peristiwa rata-rata 1,66 kategori cukup, b) permainan alur rata-rata 66,88 kategori cukup; dan 5) gaya bahasa skor rata-rata 71,63 kategori cukup.Kata kunci: cerita pendek, kemampuan, menulis.